2004
DOI: 10.1158/1078-0432.ccr-04-1568
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitor, Fluvastatin, as a Novel Agent for Prophylaxis of Renal Cancer Metastasis

Abstract: Conclusions: Because our results suggest that fluvastatin may effectively inhibit in vitro tumor growth, invasion, angiogenesis, and metastasis of Renca cells, oral administration of fluvastatin could be a novel, safe, and effective agent for preventing metastasis of renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 24 publications
5
76
2
Order By: Relevance
“…In general, various cancers are sensitive to statin treatment (33)(34)(35). Similarly, ovarian cancer cells may be sensitive to simvastatin treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…In general, various cancers are sensitive to statin treatment (33)(34)(35). Similarly, ovarian cancer cells may be sensitive to simvastatin treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…Horiguchi and colleagues demonstrated that oral fluvastatin, administered at the recommended doses for hypercholesterolemia, markedly suppressed metastasis in a mouse model of RCC. 60 Their in vitro data linked fluvastatin effects to the induction of cell arrest and apoptosis as well as to an inhibitory effect on angiogenesis and invasion. 60 In another study, Woodard and colleagues demonstrated that statins suppress activation of the mTOR pathway in RCC cells via inhibition of Akt activation.…”
Section: Statinsmentioning
confidence: 99%
“…60 Their in vitro data linked fluvastatin effects to the induction of cell arrest and apoptosis as well as to an inhibitory effect on angiogenesis and invasion. 60 In another study, Woodard and colleagues demonstrated that statins suppress activation of the mTOR pathway in RCC cells via inhibition of Akt activation. 61 Although, to our knowledge, there are no data yet to show whether statins can reduce cholesterol accumulation in RCC and whether that by itself has a tumour-suppressive effect, the data suggest a rationale to prospectively examine the role of statins in chemoprevention of primary RCC and against the potential recurrence of the disease following surgical removal of the primary tumour in an adjuvant setting.…”
Section: Statinsmentioning
confidence: 99%
“…24 Briefly, cells infected with L-GFP or L-NEP at MOI 10 for 48 h were trypsinized, and a cell suspension of 2 Â 10 5 cells in 500 ml of serum-free medium was added to the insert and 750 ml of medium containing 10% FCS was added to the lower chamber. Following incubation for 24 h at 371C, membranes were fixed and stained using Diff-Quik Stain Set (Dade Behring, Inc., Deerfield, IL), and the numbers of invaded cells were determined at 40-fold magnification in at least 10 fields of each well.…”
Section: Matrigel Invasion Assaymentioning
confidence: 99%